Pro Python - Alchin, Marty (Apress, 2012)
When I wrote my first book, Pro Django, I didn’t have much of an idea what my readers would find interesting. I had gained a lot of information I thought would be useful for others to learn, but I didn’t really know what would be the most valuable thing they’d take away. As it turned out, in nearly 300 pages, the most popular chapter in the book barely mentioned Django at all. It was about Python.